The five key "ingredients" for improving outcomes in cardiogenic shock complicating acute myocardial infarction. Issue 3 (20th February 2018) - Brilakis, Emmanouil S.; Eckman, Peter
Key Points: Cardiogenic shock in the setting of acute myocardial infarction (AMICS) carries high mortality. A systematic, protocol‐driven, approach to AMICS may improve outcomes. The 5 key "ingredients" for the managements of AMICS are: (a) early diagnosis; (b) hemodynamic assessment; (c) culprit‐only coronary revascularization; (d) judicious use of mechanic circulatory support; (e) expert in‐hospital treatment.